2019
DOI: 10.1039/c8ta10822f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced catalytic benzene oxidation over a novel waste-derived Ag/eggshell catalyst

Abstract: Ag nanoparticles loaded-eggshell catalysts were successfully synthesized by a simple impregnation method, in which the trashy eggshell was served as both biotemplate and support. The eggshell supported Ag catalyst exhibit excellent catalytic activity and stability for benzene oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 54 publications
5
62
0
1
Order By: Relevance
“…By in situ FTIR analysis, it is determined that active oxygen species in the catalyst directly participate in the reaction. The prepared catalyst was stable with constant benzene conversion of 95% during 50 h. Similar research was conducted by Guo et al ( 2019 ) with eggshell-supported Ag catalyst. It was determined that optimal Ag concentration for this process was 19.9%, whereas the necessary oxidation temperature was lower (225°C) than in the case of Co 3 O 4 /eggshell-catalyzed process.…”
Section: Eggshell In Catalysissupporting
confidence: 78%
See 2 more Smart Citations
“…By in situ FTIR analysis, it is determined that active oxygen species in the catalyst directly participate in the reaction. The prepared catalyst was stable with constant benzene conversion of 95% during 50 h. Similar research was conducted by Guo et al ( 2019 ) with eggshell-supported Ag catalyst. It was determined that optimal Ag concentration for this process was 19.9%, whereas the necessary oxidation temperature was lower (225°C) than in the case of Co 3 O 4 /eggshell-catalyzed process.…”
Section: Eggshell In Catalysissupporting
confidence: 78%
“…These studies have demonstrated that eggshell-based catalysts outperformed other types of support materials (i.e., commercial CaCO 3 ; Guo et al, 2019 ; Li et al, 2020 and oyster shell; Li et al, 2020 ) as well as pure NPs (Guo et al, 2019 ; Li et al, 2020 ). Moreover, Guo et al showed that Pt NPs/eggshell exhibited a more preferable catalytic activity compared to that of commercial 5Pt/C catalyst (Guo et al, 2020 ).…”
Section: Eggshell In Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of these eggshells, collected greatly every day, as an alternative source of CaCO 3 , will help reduce the risk of microbiological and toxic problems, and may reduce the impact on the natural reserves of limestone, non-renewable natural sources. There are several extensive reviews of the applications of eggshells [9][10][11][12][13] . Several ways have been reported to manage eggshells waste typically destined for land ll and some others such as soil conditioner, fertilizer, animal feed, additive food, adsorbent, calcium supplement, paper manufacture, and material re-used through recycling, all having the potential to be more sustainable methods 3,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] As a typical noble metal, Ag has successfully attracted extensive current research interest in the wastewater treatment eld, since Ag provides sufficient active sites for the degradation of harmful pollutants and accelerates the degradation of the pollutant. [20][21][22][23] By far, various kinds of synthetic strategies, such as electrochemical, decomposition, microwave assisted technology and wet chemical, have been designed for the fabrication of binary Ag/ZnO, but they are generally costly, ammable and toxic. [24][25][26][27][28][29][30] Therefore, developing an efficient and environmentally friendly route to prepare binary Ag/ZnO is urgently required.…”
Section: Introductionmentioning
confidence: 99%